Diseño arquitectónico universidad del Alto Ariari (2020)
This work seeks to explain and reason regarding the importance of offering higher education in the municipality of San Martín Meta, the objective is to guarantee to the youth population the access to the project of the Universidad del Alto del Ariari, supporting through agricultural, agronomic, agri-environmental and other related careers the economic and social development of the municipality. In turn, this will allow the conservation of the environment and the proper use of knowledge: through research and practice, which linked to concepts such as conservation, recovery, integration and sustainable development gives as collateral benefit the agricultural research and training. Seeking to generate new ideas about agricultural territories so that they are a transitional element between the countryside and the urban area. Due to date, the development of a college for the professional development of the community has not been managed; conditions such as the lack of infrastructure, machinery and areas for the efficient development of education and the current academic offer in the municipality are technical studies and technologists. It is considered that the project seeks to be influential with urban and rural communities, helping to educate the population of the municipality.